Mango in Sudan - Eltoum, Sanna (2009)
Mango is one of the essential horticultural crops in Sudan. It has economic signifycance being cultivated almost around the year in different parts of the country. It has a regional and international demand due to its palatable and adored taste with great nutritive value. It has a great chance for new markets abroad.